2012
DOI: 10.1088/0004-637x/750/2/164
|View full text |Cite
|
Sign up to set email alerts
|

EVLA OBSERVATIONS CONSTRAIN THE ENVIRONMENT AND PROGENITOR SYSTEM OF Type Ia SUPERNOVA 2011fe

Abstract: We report unique EVLA observations of SN 2011fe representing the most sensitive radio study of a Type Ia supernova to date. Our data place direct constraints on the density of the surrounding medium at radii ∼ 10 15 − 10 16 cm, implying an upper limit on the mass loss rate from the progenitor system oḟ M 6 × 10 −10 M ⊙ yr −1 (assuming a wind speed of 100 km s −1 ), or expansion into a uniform medium with density n CSM 6 cm −3 . Drawing from the observed properties of non-conservative mass transfer among accret… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
266
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(289 citation statements)
references
References 93 publications
21
266
2
Order By: Relevance
“…Additionally, SN 2011fe, a SN Ia which exploded in a nearby galaxy, showed no evidence of interaction with circumstellar material at radio, X-ray, and optical wavelengths (e.g. Margutti et al 2012;Chomiuk et al 2012;Patat et al 2013), and pre-explosion images exclude most types of donor stars of the SD channel (Li et al 2011a). A&A 563, A83 (2014) These difficulties in reconciling the observational evidence with the predictions of the SD channel are avoided in the DD channel, but this channel has its own difficulties.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, SN 2011fe, a SN Ia which exploded in a nearby galaxy, showed no evidence of interaction with circumstellar material at radio, X-ray, and optical wavelengths (e.g. Margutti et al 2012;Chomiuk et al 2012;Patat et al 2013), and pre-explosion images exclude most types of donor stars of the SD channel (Li et al 2011a). A&A 563, A83 (2014) These difficulties in reconciling the observational evidence with the predictions of the SD channel are avoided in the DD channel, but this channel has its own difficulties.…”
Section: Introductionmentioning
confidence: 99%
“…This has been suggested to be evidence that supports the SD scenario because such CSM is generally expected to exist around SN Ia progenitor as the result of mass transfer from the companion star, as well as from WD winds. On the other hand, there is some evidence in favour of the DD scenario, e.g., the nondetection of pre-explosion companion stars in normal SNe Ia (Li et al 2011;Bloom et al 2012), the absence of H/He features in the nebular spectra of SNe Ia (Leonard 2007;Lundqvist et al 2013Lundqvist et al , 2015Shappee, Kochanek & Stanek 2013;Maguire et al 2016), the lack of radio and X-ray emission around peak brightness (Bloom et al 2012;Brown et al 2012;Chomiuk et al 2012;Horesh et al 2012;Margutti et al 2014), and the absence of a sur-viving companion star in SN Ia remnants (Kerzendorf et al 2009;Schaefer & Pagnotta 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Using more recent radio observations, Chomiuk et al (2011) analyzed EVLA observations of early SN Ia spectra. From their non-detections, they found typical upper limitsṀ/u w 10 −7 M yr −1 /(100 km s −1 ) for most sources (private communication).…”
Section: Upper Limitsmentioning
confidence: 99%
“…From their non-detections, they found typical upper limitsṀ/u w 10 −7 M yr −1 /(100 km s −1 ) for most sources (private communication). Chomiuk et al (2012) reported upper limits ofṀ/u w = (6 × 10 −10 −3 × 10 −9 ) M /yr/(100 km s −1 ) for non-detections of radio emission from SN2011fe, the closest SN Ia in 25 years. For the lower wind speed used in our model, the upper limits are correspondingly lower, hence the upper limit of the wind mass-loss rate of the donor becomes 10 −8 M yr −1 for typical SD SN Ia progenitors, and (6 × 10 −11 −3 × 10 −10 ) M /yr for SN2011fe.…”
Section: Upper Limitsmentioning
confidence: 99%